Impact of pre‐therapy glioblastoma multiforme microenvironment on clinical response to autologous CMV‐specific T‐cell therapy. Issue 11 (5th November 2019) - Walker, David G; Shakya, Reshma; Morrison, Beth; Neller, Michelle A; Matthews, Katherine K; Nicholls, John; Smith, Corey; Khanna, Rajiv
Abstract: Objectives: Clinical response to antibody‐based immunotherapies targeting checkpoint inhibitors is critically dependent on the tumor immune microenvironment (TIME). However, the precise impact of the TIME on adoptive cellular immunotherapy remains unexplored. Here we have conducted a long‐term follow‐up analysis of patients with recurrent glioblastoma multiforme (GBM) who were treated with autologous CMV‐specific T‐cell therapy to delineate the potential impact of the TIME on their clinical response. Methods: Multiplexed immunohistochemical analysis of CD3, PD‐L1 and Sox‐2 in GBM tissue biopsies obtained before autologous T‐cell therapy was carried out and correlated with long‐term survival of GBM patients adoptively treated with T‐cell therapy. Results: Tumor microenvironment analyses revealed that the pre‐treatment cellular composition of the tumor tissue may influence the subsequent response to adoptive T‐cell therapy. GBM patients who showed prolonged overall survival following T‐cell therapy had a significantly lower number of tumor‐infiltrating CD3 + T cells in recurrent tumors than that in patients with short‐term survival. Furthermore, long‐term surviving patients showed low or undetectable PD‐L1 expression in tumor cells in recurrent GBM biopsies. Conclusion: We hypothesise that lack of PD‐L1‐mediated immunosuppression in the TIME may allow efficient immune control following adoptive T‐cell therapy. Future studies combining anti‐PD‐L1 or genetically modified T cells with PD‐1 receptor knockdown could be considered to improve clinical responses in patients who have high PD‐L1 expression in their tumors. Abstract : The precise role of tumor immune microenvironment (TIME) on clinical response to adoptive cellular immunotherapies remains largely unexplored. In this paper, we have analysed the impact of TIME on the clinical response of glioblastoma patients who showed either long‐term or short‐term overall survival following adoptive T‐cell therapy.